2006
DOI: 10.1080/13880200600897106
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Antimicrobial Activity of the Essential Oil ofThymus fontanesii.

Abstract: The yield of oil isolated by hydrodistillation from aerial parts of Thymus fontanesii Boiss. et Reut. (Lamiaceae) growing wild in Djelfa (Algeria) was 0.9%. Analysis of the oil by gas chromatography (GC) and gas chromato-graphy=mass spectrometry (GC=MS) revealed the identification of 47 components accounting for 98.5% of the total oil. The oil was found to be rich in monoterpenes (91.5%) with major constituents being thymol (29.3%), c-terpinene (21.7%), p-cymene (15.9%), and thymol methyl ether (11.4%), while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
2
15
0
3
Order By: Relevance
“…However, the same plant gives an essential oil whose composition differs according to the localization; indeed, the major constituents are linalool at 43.3%, thymol at 29.2%, and p‐cymene at 6.8% in the region of Djelfa, while in the region of Setif the major compound is Thymol. (67.8%) followed by γ‐terpinene (15.9%) and p‐cymene (13.0%) (Dob, Dahmane, Benabdelkader, & Chelghoum, ; Ghannadi, Sajjadi, Kabouche, & Kabouche, ). The investigation of Djouahri et al proved that the geographic origin of the plants has a significant effect on their chemical composition (Djouahri, Saka, Boudarene, & Baaliouamer, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the same plant gives an essential oil whose composition differs according to the localization; indeed, the major constituents are linalool at 43.3%, thymol at 29.2%, and p‐cymene at 6.8% in the region of Djelfa, while in the region of Setif the major compound is Thymol. (67.8%) followed by γ‐terpinene (15.9%) and p‐cymene (13.0%) (Dob, Dahmane, Benabdelkader, & Chelghoum, ; Ghannadi, Sajjadi, Kabouche, & Kabouche, ). The investigation of Djouahri et al proved that the geographic origin of the plants has a significant effect on their chemical composition (Djouahri, Saka, Boudarene, & Baaliouamer, ).…”
Section: Resultsmentioning
confidence: 99%
“…gives an essential oil whose composition differs according to the localization; indeed, the major constituents are linalool at 43.3%, thymol at 29.2%, and p-cymene at 6.8% in the region of Djelfa, while in the region of Setif the major compound is Thymol. (67.8%) followed by g-terpinene (15.9%) and p-cymene (13.0%) (Dob, Dahmane, Benabdelkader, & Chelghoum, 2006;Ghannadi, Sajjadi, Kabouche, & Kabouche, 2004…”
Section: Chemical Composition Of the Essential Oil Of T Fontanesiimentioning
confidence: 99%
“…These species have also been used as carminative, diuretic, urinary disinfectant and vermifuge (Matta et al, 2007). The antioxidant and antimicrobial activity of members of the genus Thymus, including the wellknown specie, Thymus vulgaris, has been widely reported (Dob, Dahmane, Benabdelkader, & Chelghoum, 2006;Marino, Bersani, & Comi, 1999;Ryman, 1992;Schwarz, Ernst, & Ternes, 1996). The essential oils and extracts of many Thymus species are widely used in pharmaceutical, cosmetic and perfume industry, and for flavouring and preservation of several food products (Bauer, Garbe, & Surburg, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Thymus fontanesii essential oil (TFEO) revealed that carvacrol and thymol represent the most important compounds in the species flowed by p-cymene and γterpinene [5][6][7][8][9]. Concerning the biological properties of T. fontanesii essential oil, there are some studies on the antimicrobial activity [7][8][9], antidermatophytic activity [10] and anti-inflammatory activity [6,8], but there are not studies on their antioxidant activity.…”
Section: Some Reports On the Chemical Composition Ofmentioning
confidence: 99%